1993
DOI: 10.1016/1010-7940(93)90070-r
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial damage of the venous graft in CABG *1Influence of solutions used for storage and rinsing on endothelial function

Abstract: A significant proportion of early graft occlusions after aortocoronary revascularization using autologous saphenous vein grafts (SVG) are due to mechanical and/or metabolic or biochemical endothelial lesions. The morphological examination of the endothelium, usually carried out using light microscopy or by various types of scanning electron microscopy (SEM), does not give any indication of the functioning of the endothelium (E). Functionally intact E is capable of producing endothelium-derived relaxing factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
1
13
0
2
Order By: Relevance
“…This is in accord with the results of other groups [16,17]. Zerkowski et al showed a greater degree of dissociation of the endothelial cells and an altered surface structure in saline solution-stored vessel segments studied with scanning electron microscopy [17]. In this context, it is noted here that the frequently added heparin may exert additional toxic effects on the endothelial layer and therefore should be avoided [18,19].…”
Section: [ ( ) T D $ F I G ]supporting
confidence: 91%
See 2 more Smart Citations
“…This is in accord with the results of other groups [16,17]. Zerkowski et al showed a greater degree of dissociation of the endothelial cells and an altered surface structure in saline solution-stored vessel segments studied with scanning electron microscopy [17]. In this context, it is noted here that the frequently added heparin may exert additional toxic effects on the endothelial layer and therefore should be avoided [18,19].…”
Section: [ ( ) T D $ F I G ]supporting
confidence: 91%
“…Frequently used options are HTK solution, Ringer's lactate solution, PSS, or blood augmented with heparin [16]. Several studies have indicated the superiority of HTK solution or heparinized blood in comparison to the reported alternatives [16,17]. However, more recently, a poor preservation of HTK solution with respect to coronary artery function has been reported [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saphenous veins and internal mammary arteries were obtained during cardiopulmonary bypass. Immediately after excision, all specimens were placed in autologous heparinized whole blood (Zerkowski et al 1993) and kept overnight in the refrigerator.…”
Section: Methodsmentioning
confidence: 99%
“…The aortic rings were then washed with freshly prepared Krebs Henseleit buffer pH 7.4 and the tension was readjusted to 1.5 g tension. Each preparation was sub-maximally contracted using 3 μl of 0.1 mM NE (0.3 μM final concentration) [15, 32]. Those aortic rings that failed to contract were discarded.…”
Section: Methodsmentioning
confidence: 99%